The Impact of Prenatal Exposure to Power Plant Emissions on Birth Weight: Evidence from a Pennsylvania Power Plant Located Upwind of New Jersey. (4th April 2017) - Yang, Muzhe; Bhatta, Rhea A.; Chou, Shin‐Yi; Hsieh, Cheng‐I
Abstract: To examine the infant health impact of prenatal exposure to power plant emissions, we draw scientific evidence on the impacted region downwind of a large polluter, a coal‐fired power plant located on the border of two states and proven to be the sole contributor to the violation of air quality standards of the impacted region. Our results show that among all live singleton births that occurred during 1990 through 2006, those born to mothers living as far as 20 to 30 miles away downwind from the power plant (which is also an affluent region) during pregnancy are at greater risks of low birth weight (LBW) and very low birth weight (VLBW): the likelihoods of LBW and VLBW could increase approximately by 6.50 and 17.12 percent, respectively. In light of the continual efforts of The U.S. Environmental Protection Agency in reducing cross‐state air pollution caused by transboundary power plant emissions, our study is aimed at broadening the scope of cross‐border pollution impact analysis by taking into account adverse infant health effects of upwind polluters, which can impose disproportionate burdens of health risks on downwind states due to air pollutants transported by wind.